OPTIMALISASI PENDAPATAN PAJAK RESTORAN OLEH BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH DI KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Ramadhanti, Medina; Meiwanda, Geovani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Restaurant tax revenue in Pangkalan Kerinci Subdistrict, Pelalawan Regency has decreased in recent years, this is due to the absence of an inventory of tax recipients, limited operational tax collection and collection, weak monitoring mechanisms, socialization of tax collection involving sub-districts has not been evenly distributed so that people receive restaurant tax information. very limited, and guidance to taxpayers. Optimizing restaurant tax revenue is a step forward made by the Regional Financial and Asset Management Agency of Pelalawan Regency to increase restaurant tax, especially in Pangkalan Kerinci District. This study aims to present the optimization analysis that has been carried out so that it shows the analysis of the inhibiting factors of optimizing restaurant tax revenue in Pangkalan Kerinci District. To achieve this goal, this study uses interactive analysis techniques with qualitative research using a descriptive approach and the required data, both primary and secondary data, are obtained through observation, interviews, and documentation and then analyzed based on the research problem. This research shows that first, the optimization of restaurant tax revenue in Pangkalan Kerinci District in this study is not maximizing restaurant tax. Second, the inhibiting factors are operational limitations, executive capabilities, and lack of public awareness in paying restaurant taxes in Pangkalan Kerinci District.Keywords: Optimization, Public Organization, Restaurant Tax.